Growth parameters of InAs/GaAs quantum dots grown by MOVPE - Roslan, Sharizar; Othaman, Zulkafli; Muhammad, Rosnita; Lim, Kheng Boo (Faculty of Science, University Teknologi Malaysia, 2006)
Quantum dots are zero dimensional structures and therefore have superior transport and optical properties compared to either 2-dimensional or 3-dimensional structures. Quantum dots show promise for use in diode lasers, amplifiers, and biological sensors. They are also vigorously researched for use in solid-state quantum computing. Indium arsenide quantum dots are currently studied for their use in the photoelectronic and semiconductor fields. In our research, Indium Arsenide (InAs) quantum dots are grown on Gallium Arsenide (GaAs) substrate using Metal Organic Vapor Phase Epitaxy (MOVPE) in the Stranski-Krastanov Growth mode. Several parameters influence the growth of InAs quantum dots greatly. We will be describing these growth parameters, which we have identified in our current growth attempts. We are currently trying to achieve device quality InAs/GaAs quantum dots by varying these parameters we have identified. These growth parameters include the V/III ratio of both InAs and GaAs, In/As growth temperature, and quantum dot growth time. By carefully fine tuning the parameters above, we will be able to grow device quality quantum dots. Deviations from the optimized value will result in either no formation of quantum dots, or the formation of large islands which are particularly susceptible to dislocations. The effects of differing growth parameters are observed by using an Atomic Force Microscope (AFM) located at Faculty of Science, UTM. The MOVPE is located at Ibn Sina Institute for Fundamental Science Studies, UTM.